Pendampingan Musabaqah Tilawatil Qur’an di Taman Pendidikan Al-Qur’an Babul Maghfirah Gunong Kleng, Aceh Barat - Azmi, Ulil (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2025)
The mentoring program for the Qur'an Recitation Competition (MTQ) at TPQ Babul Maghfirah, West Aceh, was conducted to assist students in preparing for the competition. This study aims to describe the mentoring process, identify supporting and inhibiting factors, and analyze its impacts. Using the Participatory Action Research (PAR) method, data was collected through observation, interviews, and documentation. The results indicate that the mentoring program encompasses candidate selection processes, participant training and coaching, and competition simulations. Supporting factors include students' enthusiasm and parental support, while time constraints and limited facilities emerge as primary challenges. This mentoring program is expected not only to enhance competition performance but also to deepen students' connection with the Qur'an. The findings recommend collaboration with local stakeholders for sustainable program development.